Population Dynamics Of Rattans (Arecaceae, Subfamily Calamoideae) Through Fruit Utilization And Seed Distribution By Frugivorous Mammals - Nadine, Ruppert (2014)
Many rattan species have a high economic value and thus became threatened by overexploitation in the wild. This study assesses rattan diversity, abundance and biomass change and identifies main mammal seed dispersers of rattans in a lowland Dipterocarp rain forest of West-Malaysia during a three-years study period. It also adresses seedling development and general flowering and fruiting events whereof a more detailed look on one species, namely Calamus castaneus, is taken. All rattan clusters within the study plots (12.2 ha) were GPS-tagged and their stems counted. By means of video-traps at rattan frutescenses and seed stations their main mammal fruit and seed utilizers were identified. Population sizes, home ranges, moving patterns, and maximum seed dispersal ability were analysed by executing a mark and recapture study of small mammals and by means of radio-tracking of the primate species Macaca nemestrina. In total twelve rattan species of five genera comprising almost 2000 stems with a mean biomass of 3.1 t ha-1 were surveyed. The five most abundant species were Daemonorops angustifolia (39.0 stems ha-1), Calamus castneus (31.5 stems ha-1), D. micracantha (29.3 stems ha-1), D. calicarpa (17.9 stems ha-1), and Cerotolobus subangulatus (10.3 stems ha-1).